Does hormonal contraception during molar pregnancy follow-up influence the risk and clinical aggressiveness of gestational trophoblastic neoplasia after controlling for risk factors? - Sobral Dantas, Patricia Rangel [UNESP]; Maesta, Izildinha [UNESP]; Rezende Filho, Jorge; Amin Junior, Joffre; Elias, Kevin M.; Howoritz, Neil; Braga, Antonio; Berkowitz, Ross S. (Elsevier B.V., 2017)
Objective. To evaluate the influence of hormonal contraception (HC) on the development and clinical aggressiveness of gestational trophoblastic neoplasia (GTN) and the time for normalization of human chorionic gonadotropin (hCG) levels. Methods. A retrospective cohort study was conducted with women diagnosed with molar pregnancy, followed at the Rio de Janeiro Trophoblastic Disease Center, between January 2005 and January 2015. The occurrence of postmolar GTN and the time for hCG normalization between users of HC or barrier methods (BM) during the postmolar follow-up or GTN treatment were evaluated. Results. Among 2828 patients included in this study, 2680 (95%) used HC and 148 (5%) used BM. The use of HC did not significantly influence the occurrence of GTN (ORa: 0.66, 95% CI: 0.24-1.12, p = 0.060), despite different formulations: progesterone-only (ORa: 0.54, 95% CI: 0.29-1.01, p = 0.060) or combined oral contraception (COC) (ORa: 0.50, 95% CI: 0.27-1.01, p = 0.60) or with different dosages of ethinyl estradiol: 15 mcg (ORa, 1.33, 95% CI 0.79-2.24, p = 0.288), 20 mcg (ORa: 1.02, 95% CI: 0.64-1.65, p = 0.901), 30 mcg (ORa: 1.17, 95% Cl: 0.78-1.75, p = 0.437) or 35 mcg (ORa: 0.77, 95% CI: 0.42-1.39, p = 0.386). Time to hCG normalization weeks (ORa: 0.58, 95% CI: 0.43-1.08, p = 0.071) or time to remission with chemotherapy 14 weeks (ORa: 0.60, 95% CI: 0.43-1.09, p = 0.067) did not significantly differ among HC users when compared to patients using BM, when controlling for other risk factors using multivariate logistic regression. Conclusions. The use of HC during postmolar follow-up or GTN treatment does not seem to increase the risk of GTN or its severity and does not postpone the normalization of hCG levels. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Molar pregnancy; Contraception; Gestational trophoblastic neoplasia